Clinical efficacy and tolerability of Esketamine: a case series. (1st June 2022) - Passani, C.; Ragone, N.; Congedo, C.M.; Barbini, B.; Zanardi, R.; Cavallini, M.C.; Colombo, C.
Abstract : Introduction: Esketamine is a novel antidepressant approved by the FDA in 2019 in the form of an intranasal spray, recommended for Treatment-Resistant Depression (TRD). The intranasal spray system appears to be more manageable than intravenous ketamine infusion. It contains ketamine's S- isomer which is four-fold more potent for the NMDA receptor. Objectives: The aim of this case series is to describe our clinical experience in the use of Esketamine. Methods: 6 TRD patients (3 men; 3 women) were recruited in San Raffaele Turro Hospital from March 2021. All patients (2 bipolar and 4 unipolar) were diagnosed with a Major Depressive Episode according to DSM-5 criteria, resistant to at least two antidepressants. Initially, Esketamine was administrated twice weekly for one month; afterward, it was administrated once weekly for a month; finally, it was administrated once weekly or every two weeks for a month. Clinical scales (HAM-D, YMRS, SSI, HAM-A, MADRS, CADSS) were administrated to assess symptoms and sides effects before and after each administration on a weekly basis. Results: Three patients out of six showed an improvement in depressive symptoms: two patients had remission (final HAM-D score < 8); one patient had a clinical response (final HAM-D score < 50 % respect baseline value). Three patients withdrew the treatment: two for perceived inefficacy, after 16 and 19 administrations, one for personal reasons. Conclusions: The use of Esketamine in our TRD patients showed good effectiveness and tolerability but randomized controlled clinical trials are needed to confirm our findings. Disclosure: No significant relationships.